2017
DOI: 10.1159/000453005
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin during the Last Hour of the Hemodialysis Session: A Pharmacokinetic Analysis

Abstract: Background: Vancomycin is usually administered after the dialysis sessions to patients undergoing hemodialysis. Administration of vancomycin during (as opposed to after) sessions would save time, and would be more acceptable to patients and staff, but may lead to vancomycin underexposure. The aim of this study was to propose a new dosing regimen of vancomycin taking into account the dialysis-related losses of vancomycin when administered during dialysis. Methods: In this monocentric prospective study, vancomyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 19 publications
2
15
1
Order By: Relevance
“…Nyman et al reported that 35% of the dose would be removed and suggested to increase the dose to account for the intradialytic vancomycin removal . Similarly, Ghouti‐Terki et al reported a 25% percent less exposure to vancomycin recommending to empirically increase the dose to account of amount removed by dialysis. These findings match our current protocol .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nyman et al reported that 35% of the dose would be removed and suggested to increase the dose to account for the intradialytic vancomycin removal . Similarly, Ghouti‐Terki et al reported a 25% percent less exposure to vancomycin recommending to empirically increase the dose to account of amount removed by dialysis. These findings match our current protocol .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ghouti‐Terki et al reported a 25% percent less exposure to vancomycin recommending to empirically increase the dose to account of amount removed by dialysis. These findings match our current protocol . However, Hui et al suggested to use LD and MD ranged between 1500 and 4500 mg.…”
Section: Discussionmentioning
confidence: 99%
“…There have been attempts to develop regimens for vancomycin administration during dialysis . Vancomycin can be administered during HD when using high‐flux cellulose acetate, cellulose triacetate, and polysulfone membranes if the dose is modified .…”
Section: Introductionmentioning
confidence: 99%
“…Vancomycin hydrochloride is a glycopeptide antibiotic (MW 5 1485 Daltons), which is frequently used to treat gram-positive infections in patients on chronic hemodialysis (HD), 1 and is administered either after a dialysis session or during the last hour of HD. [2][3][4] Both low-flux and high-flux membrane dialysis removes considerable amounts of vancomycin, although the median percentage removed by low-flux membrane dialysis is about 17%, and high-flux membrane dialysis is about 31%. 5 Dialysis therapy has been evolving with time, with majority of dialysis now being done using high-flux membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation